Adjustable coffee table by using wooden pallet (pinus radiata) / Siti Nurul Afeeda Nazeree - Nazeree, Siti Nurul Afeeda (Faculty of Applied Sciences, 2017)
Furniture is a movable thing which is needed in residents, office or in other locations to support various human activities such as such seating and commonly limited to one single function only. It caused less flexibility to consumers in term of body measurement. There also depleting supply of rubber wood that cause higher production cost and it is a need to find an alternative raw material to replace it. The purposes of this study are to design an Adjustable Coffee Table by using wooden pallet (Pinus radiata) and produce it at economical price. After design and production process completed, a survey was undertaken to 80 correspondents around Bandar Pusat Jengka based on different types of gender, gender, and profession. Seven characteristics of the product were evaluated such as suitability and stability of the material, design, adjustable concept, ergonomic and anthropometric, price and commercialization. The results show that there are significant different for all characteristics except for stability, design and commercialization based on gender. Meanwhile, age and profession were totally not influence the evaluation for all characteristics. So it can conclude that wooden pallet can be a suitable material to produce this adjustable coffee table. Overall this product has a potential to be commercialize to the industry with economical price.